Study of soft magnetic iron-cobalt alloys manufactured by powder injection molding = - Estudio de aleaciones magnéticas suaves de hierro-cobalto fabricadas por moldeo de polvos por inyección (2006)
Phenomenon of magletism becomes an important research field, since industry and technology demand everyday more magnetic materials for diverse applications due to their versatility. Soft magnetic materials are characterized by high magnetic inductions at Iow applied magnetic fields, with Iow coercivity fields. Among them, iron-cobalt alloys stand out for the highest magnetic saturation induction within all known materials, as well as their high Curie temperature and high magnetic permeability values. However, this alloy has a high brittleness, which with the addition of 2% of vanadium, it is reduced, since vanadium slows ordering reaction in the FeCo BCC structure and allows ductility to be retained through heat treatments. Currently, FeCo-2V alloy continues being processed, even by methods near net shape like powder injection molding (PIM). The company Steelinject S.A. uses it to manufacture a component for fuel injection pumps for diesel engines, through injection of prealloyed powder, with high temperature vacuum termal debinding and sintering processes after injection...